Food protein-induced enterocolitis syndrome: Healthcare utilization and referral patterns among a pediatric cohort - Pier, Jennifer; Bingemann, Theresa; Badwal, Jasdeep; Rosloff, Daniel; Pasha, Muhammad; Wang, Hongyue; Lomas, Jeanne M.; Järvinen, Kirsi M. (Frontiers in Allergy, 2023)
Background Food protein–induced enterocolitis syndrome (FPIES) is a non-IgE mediated food allergy characterized by delayed, repetitive vomiting. FPIES is improving in recognition; however, there remains a lag in diagnosis. This study aimed to further explore this lag, as well as referral patterns and healthcare utilization, to help determine areas for earlier recognition. Methods A retrospective chart review of pediatric FPIES patients at two hospital systems in New York was completed. Charts were reviewed for FPIES episodes and healthcare visits prior to diagnosis, and reason/source of referral to an allergist. A cohort of patients with IgE-mediated food allergy was reviewed for comparison of demographics and the time to the diagnosis. Results In total, 110 patients with FPIES were identified. The median time to diagnosis was 3 months, vs. 2 months in IgE-mediated food allergy (p < 0.05). Most referrals were from the pediatrician (68%) or gastroenterology (28%), none were from the ED. The most common reason for referral was concern of IgE-mediated allergy (51%), followed by FPIES (35%). There was a statistically significant difference in race/ethnicity between the FPIES cohort and IgE-mediated food allergy group (p < 0.0001), with a greater proportion of Caucasian patients in FPIES vs. IgE-mediated food allergy cohort. Conclusion This study demonstrates a lag in the diagnosis of FPIES and a lack of recognition outside of the allergy community, as only one-third of patients were considered to have FPIES prior to an allergy evaluation.